Impact of genetic polymorphisms of drug transporters ABCB1 and ABCG2 and regulators of xenobiotic transport and metabolism PXR and CAR on clinical efficacy of dasatinib in chronic myeloid leukemia - Madejczyk, Anna Marta; Canzian, Federico; Góra-Tybor, Joanna; Campa, Daniele; Sacha, Tomasz; Link-Lenczowska, Dorota; Florek, Izabela; Prejzner, Witold; Całbecka, M.; Rymko, M.; Dudziński, M.; Orzechowska, Magdalena Julita; et al. (Frontiers in Oncology, 2022)
Abstract Introduction: Functional single nucleotide polymorphisms (SNPs) in genes regulating cellular uptake, elimination and metabolism of xenobiotics may potentially influence the outcome of chronic myeloid leukemia (CML) patients treated with BCR-ABL1 tyrosine kinase inhibitors (TKI). Dasatinib, second generation TKI, is a substrate of the ABC-superfamily xenobiotic transporters ABCB1 (MDR1, Pg-P) and ABCG2 (BCRP). Pregnane X receptor (PXR, NR1I2) and constitutive androstane receptor (CAR, NR1I3) are involved in the control of expression of ABCB1 and ABCG2. Aim of the study: In this study we assessed the impact of inherited variants in ABCB1, ABCG2, PXR and CAR genes on dasatinib efficacy and toxicity in CML Materials and methods: Sixty-one tagging SNPs in ABCB1, ABCG2, PXR and CAR genes were analyzed by Real-Time Quantitative PCR with specific probes in 86 CML patients who failed imatinib therapy. Results: We found the associations between SNPs rs7787082 (ABCB1, OR=0.2; 95%CI=0.06-0.66, p=0.008), rs12505410 (ABCG2, OR=3.82; 95%CI=1.38-10.55;p=0.010) and rs3114018 (ABCG2, OR=0.24; 95%CI=0.08-0.71; p=0.010) and probability of achieving CCyR. Progression free survival (PFS) was significantly influenced by SNPs rs3732357 (HR=0.2, 95%CI=0.26-0.70;p=0.001) , rs3732360 (HR=0.59; 95%CI=0.38-0.93; p=0.020), rs11917714 (HR=0.58; 95%CI=0.36-0.92; p=0.020), rs3732359 (HR=0.57; 95%CI=0.36-0.91; p=0.024) in PXR, rs2307418 (HR=2.02; 95%CI=1,19-3.43; p=0.048) in CAR, rs2235023 (HR=2.49; 95%CI=1.13-5.50; p=0.011) and rs22114102 (HR=1.90; 95%CI=1.00-3.63; p=0.028) in ABCB1. Overall survival (OS) was impacted by rs3842 (HR=1.84; 95%CI=1.01-3.33; p=0.012) and rs2235023 (HR=2.28; 95%CI=1.03=5.02; p=0.027) in ABCB1, rs11265571 (HR=1.59; 95%CI=0.82-3.08; p=0.037) and rs2307418 (HR=73.68; 95%CI=4.47-1215.31; p=0.003) in CAR as well as rs3732360 (HR=0.64; 95%CI=0.40=1.04; p=0.049) in PXR. Taking into account influence of tested SNPs on treatment toxicity, we found that a significant relationships allele G of polymorphism in the ABCB1 rs7787082 gene (OR=4.46; 95%CI=1.38-14.39 p=0.012) and the hematological complications assuming the co-dominant gene inheritance model as well as a significant correlation between the presence of minor allele (G) of SNP rs2725256 in the ABCG2 gene (OR = 4.71; 95% CI = 1.20-18.47; p=0.026) and the occurrence of non-haematological complications in recessive gene inheritance model. Conclusion: Our data suggest that inherited variants in the genes encoding for proteins involved in the transport of xenobiotics may modify toxicity and efficacy of dasatinib therapy in CML patients.